The Effect Of Work Environment And Job Satisfaction On Work Productivity Of Production Section Employees At PT. Julang Oca Permana Gembung Estate Of North Bengkulu - Taryat Taryat; Ida Ayu Made. E. Gayatri; Nurzam Nurzam (Penerbit Jurnal Indonesia, 2022)
The company is an organization that has a purpose. One of them is looking for profit. These advantages can be achieved if the company's performance is efficient and effective. It can be described by increasing productivity. One of the important factors that can affect productivity is work environment. The work environment is said to be good if the work environment can support the work of employees. Employees feel safe, comfortable, undisturbed and feel at home at work, so employees can concentrate on their work and use their time as effectively as possible. The sampling technique in this study used survey techniques. The data obtained in this study were obtained directly from filling out a questionnaire addressed to 30 respondents. The method of analysis in this study is intended to answer the questions as well as the hypotheses proposed in the study. For statistical analysis using multiple regression analysis is a regression equation that measures the strength of the relationship between two or more variables. Based on the results of research and discussion on the effect of work environment and job satisfaction on work productivity of production section employees at PT Julang Oca Permana Gembung Estate, it can be concluded as follows 1). The results of the study show that the work environment variable on the employee productivity variable where the work environment variable (X1) has a significance value smaller than 0.05 (0.000 < 0.05) and the t value > t table (6.147 > 2 0.052) then H1 is accepted and it can be concluded that the work environment has a partial effect on employee productivity. 2) The results of the study show that the job satisfaction variable on the employee productivity variable where the work environment variable (X2) has a significance value smaller than 0.05 (0.005 < 0.05) and the t value > t table (2.494 > 2.052), then H1 accepted and it can be concluded that job satisfaction has an effect. 3) The results of the study that the work environment and job satisfaction are one of the important components in carrying out work activities, because good or bad performance of an employee one of which can be caused by his own work environment.